The Values of Local Wisdom in Amarasi Ikat Weaving as a Source of Social Studies Learning - Maria Magdalena Beatrice Sogen; Sapriya; Nana Supriatna; Kokom Komalasari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The advancement of technology has both positive and negative impacts on the character of the younger generation, who are the future leaders of the nation. To ensure that local cultural values remain strong, it is necessary to instill a love for local culture in the younger generation. One of the local cultures in the village of Teunbaun, West Amarasi, Kupang Regency, is the tradition of weaving ikat textiles. The indigenous people of Amarasi have a variety of patterns and motifs. Incorporating local wisdom values in schools can be achieved by integrating these values into the learning process. Social studies learning resources will be more engaging and have the potential to foster active involvement of students if the socio-cultural environment around the students is included in the learning process. One aspect of local wisdom that intrigued the researcher to study it as a source for social studies learning is the Amarasi ikat weaving. This research aims to 1) examine the values of local wisdom in the decorative patterns of Amarasi ikat weaving, and 2) describe the local wisdom values of Amarasi ikat weaving as a source for social studies learning. This research was conducted in Teunbaun Village, West Amarasi District, Kupang Regency, East Nusa Tenggara, using a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. Based on the research findings, the local wisdom values in the decorative patterns of Amarasi ikat weaving can be used as a source for social studies learning, providing a positive impact on shaping students' character, fostering a strong sense of identity, and forming students into a younger generation that is proud of and loves their cultural heritage